Sistem Informasi Manajemen Restaurant Berbasis Mobile Pada Resto Bukit Pasir - Nita Afriani; Ade Dwi Putra; A. Ferico Octaviansyah Pasaribu (PT. Tech Cart Press, 2023)
The menu reservation management information system that can be accessed online using mobile is developed using extreme programming methods with stages such as planning, designing, coding, and testing the system. The results of functional suitability testing were carried out on 10 respondents consisting of admins and consumers with the answer categories Yes valued 1 and No valued 0, then the resulting percentage was 98.18% and it can be concluded that respondents rated the system built as successful or by its function. Based on the results of the usability aspect test, the percentage of the test questionnaire, which is 92.88%, can be concluded according to respondents Strongly Agree that the development is appropriate.